EVALUASI PROSES PEMBUATAN PATUNG JANGIR PADA UPT PSTKP BALI – BPPT TAHUN 2014 - I Nyoman Normal (Forum Manajemen STIMI Handayani Denpasar, 2015)
The aims of this research that relate production process of jangir statue(p 11 cm, l 4 cm, t 14 cm) use stove size differently are: (1)To know the influence ofstove sizing to cost of goods manufactured loading jangir statue; (2) To know theinfluence of stove sizing to gross profit recognition jangir statue; and (3) To knowthe influence of stove sizing to inventory turnover calculationjangir statue. Theresearch results shew that: (1) The stove sizing influent of cost production loading jangir statue (p 11 cm, l 4 cm, t 14 cm). The decreasing trend ofcost of goods manufactured jangir statue (p 11 cm, l 4 cm, t 14 cm use midle size stove was 0,96%,and big size stove was 1,15%; (2) The stove sizing influent of gross profit recognitionjangir statue (p 11 cm, l 4 cm, t 14 cm). The bigger stove sizing cause bigger grossprofit jangir statue. The increasing trend ofgross profit jangir statue (p 11 cm, l 4cm, t 14 cm) use midle size stove was 7,05%, and big size stove was 15,06%; dan(3) The stove sizing did not influent of inventory turnover jangir statue (p 11 cm, l 4cm, t 14 cm). The small stove, the middle stove size, and the big stove result the sameinventory turnover, that is 21,43 times.